A comprehensive study on ring shape specimens under compressive and tensile loadings for covering the full range of I+II fracture modes of gypsum material. (December 2022) - Karimi, Hamid reza; Khedri, Ehsan; Aliha, M.R.M.; Mousavi, Amir
Abstract: Using ring-shape specimens containing two aligned cracks on the internal surface of the ring, two test configurations subjected to tensile or compressive loads namely (i) diametrically compressed ring (DCR) and (ii) diametrically tensile ring (DTR) specimens were suggested to investigate the full mixed-mode I/II fracture problem. The fracture parameters, including modes I and II stress intensity factors and T-stress, were determined numerically for these two test specimens with different crack lengths and crack angles. Also, the ability of the specimens was examined by conducting experimental fracture tests on gypsum material. In addition, the direction of fracture kinking was investigated both experimentally and theoretically. The experimental results were then compared and predicted using the mixed mode fracture criteria such as maximum tangential stress (MTS) and generalized maximum tangential stress (GMTS). The normalized fracture toughness ( K IIc /K Ic ) ratios of the tested DCR and DTR specimens were about 0.72 and 0.95, respectively. Such difference was related to the considerable effect of T -stress values and it was shown that the GMTS criterion provides more accurate predictions for the test results of both DCR and DCT samples compared to the MTS criterion.